Real estate transaction taxes and credit supply - Michael Koetter; Philipp Marek; Antonios Mavropoulos (Deutsche Bundesbank, 2021)
We exploit staggered real estate transaction tax (RETT) hikes across German states to identify the effect of house price changes on mortgage credit supply. Based on approximately 33 million real estate online listings, we construct a quarterly hedonic house price index (HPI) between 2008:q1 and 2017:q4, which we instrument with state-specific RETT changes to isolate the effect on mortgage credit supply by all local German banks. First, a RETT hike by one percentage point reduces HPI by 1.2%. This effect is driven by listings in rural regions. Second, a 1% contraction of HPI induced by an increase in the RETT leads to a 1.4% decline in mortgage lending. This transmission of fiscal policy to mortgage credit supply is effective across almost the entire bank capitalization distribution.
Keywords: H30; R00; R31; 330; Fiscal Shocks; Real Estate Markets; Mortgage Lending; Price-to-Rentratio